Paradigma Postmodernisme; Solusi untuk Kehidupan Sosial? - Iromi Ilham (Sociology Department Of Syiah Kuala University, 2018)
AbstractMost social scientists see that the presence of postmodernism is as anti-modernism, but according to the author there is no clear boundary between the